Establishment of IPv6 network on intranet environment - Bahaman, Nazrulazhar; Mas'ud, Mohd Zaki; Hamid , Erman; Abdollah, Mohd Faizal; Mat Ariff, Nor Azman (2010)
Internet Protocol version six (IPv6) is the next generation internet protocol. It is not yet possible to completely migrate to IPv6, but several transitions mechanisms are available to allow IPv6 and IPv4 coexist together in the same network infrastructure. The main benefit of this protocol is a larger address space and enhanced security options. It is not easy to migrate from current Internet Protocol version four (IPv4) to Internet Protocol version six (IPv6) as it is not “Plug n Play” since both are incompatible protocol. For smooth integration between these protocols, native IPv6 testbed (TEST6) was deployed in an intranet environment. In other hand, this gained an experience and confidence before fully integrating it with an existing Internet protocol. This paper describes how TEST6 was setup in intranet environment (TEST6-I) through numerous of process and network test performed to verify the connectivity.